2009
DOI: 10.1038/emboj.2009.307
|View full text |Cite
|
Sign up to set email alerts
|

Immature small ribosomal subunits can engage in translation initiation in Saccharomyces cerevisiae

Abstract: It is generally assumed that, in Saccharomyces cerevisiae, immature 40S ribosomal subunits are not competent for translation initiation. Here, we show by different approaches that, in wild-type conditions, a portion of pre-40S particles (pre-SSU) associate with translating ribosomal complexes. When cytoplasmic 20S pre-rRNA processing is impaired, as in Rio1p-or Nob1p-depleted cells, a large part of pre-SSUs is associated with translating ribosomes complexes. Loading of pre-40S particles onto mRNAs presumably u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 50 publications
(88 reference statements)
8
67
0
Order By: Relevance
“…2A). It is reported that the immature small ribosomal subunits can engage in translation initiation and the putative endonuclease Nob1, which is specific to late pre-40S particles can interact with polysomes (35,36). This is one possible reason why Nob1 was detected in polysome fractions.…”
Section: Resultsmentioning
confidence: 99%
“…2A). It is reported that the immature small ribosomal subunits can engage in translation initiation and the putative endonuclease Nob1, which is specific to late pre-40S particles can interact with polysomes (35,36). This is one possible reason why Nob1 was detected in polysome fractions.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent study reached the opposite conclusion: Immature 40S subunits containing 20S pre-rRNA can bind translation factors and engage in translation initiation in S. cerevisiae, although the resulting 80S is less efficient in translation and rapidly destroyed by a specialized mRNA 2 These authors contributed equally to this work. (Soudet et al 2010). In a similar vein, two very recent studies have concluded that processing of S. cerevisiae 20S pre-rRNA in fact requires the pre-40S particle to associate in the cytoplasm with both the translation initiation factor eIF5b and 60S subunit; it was suggested that this might represent the final proofreading step before 40S engages in translation (Lebaron et al 2012;Strunk et al 2012).…”
Section: Introductionmentioning
confidence: 91%
“…6, data not shown and Ref. 28). In cells lacking Dim2, some Nob1 is found free at the top of the gradient, not associated with preribosomal particles.…”
Section: Mutations In the Central Kh-like Domain Of Dim2 Reduce Nob1 mentioning
confidence: 99%